Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T17:20:03+01:00
Rozwiąż równanie i sprawdź jego winik:
a)-7x+5=11x+41
-7x -11x = 41 -5
-18x = 36
x = 36 : (-18)
x = -2

spr.
L(-2) = (-7)*(-2) + 5 = 14 +5 = 19
P(-2) = 11*(-2) + 41 = -22 + 41 = 19
L(-2) = P(-2)

b)36x-14=14x-36
36x -14x = -36 + 14
22 x = -22
x = (-22) :22
x = -1
L(-1) = 36*(-1) - 14 = -36 -14 = -50
P(-1) = 14*(-1)- 36 = -14 - 36 = -50
L(-1) = P(-1)

c)3x-4=4x
3x -4x = 4
-x = 4
x = -4
L(-4) = 3*(-4) -4 = -12 -4 = -16
P(-4) = 4*(-4) = -16
L(-4) = P(-4)

d)3x+9=-3+9
3x = 6 -9
3x = -3
x = (-3) : 3
x = -1
L(-1) = 3*(-1) + 9 = -3 + 9 = 6
P(-1) = -3 + 9 = 6
L(-1) = P(-1)

e)-27+1=2x+59
-26 = 2x + 59
-2x = 59 + 26
-2x = 85
x = 85 : (-2)
x = - 42,5
L(-42,5) = -27 + 1 = -26
P(-42,5) = 2*(-42,5) + 59 = -85 + 59 = -26
L(-42,5) = P(-42,5)

f)45x-19=19x-45
45x -19x = - 45 +19
26x = -26
x = (-26) : 26
x = -1
L(-1) = 45*(-1) - 19 = -45 -19 = -64
P(-1) = 19*(-1) - 45= -19 -45 = -64
L(-1) = P(-1)

g)82x-9=-18x+1
82x +18x = 1 +9
100 x = 10
x = 10 : 100
x = 1/10
x = 0,1
L(0,1) = 82*(0,1) - 9 = 8,2 - 9 = - 0,8
P(0,1) = -18*(0,1) + 1 = -1,8 + 1 = - 0,8
L(-0,1) = P(0,1)
2010-02-07T17:29:21+01:00
A) -7x+5=11x+41 -7x-11x=41-5 -18x=36/9-18) x=-2
b)36x-14=14x-36 36x-14x=-36+14 22 x=-22/22 x=-1
c) 3x-4=4x 3x-4x=4 -1x=4/(-1) x=-4
d) -3x+9=-3+9 -3x=6-9 -3x=-3/(-3) x=1
e) -27+1=2x+59 -2x=59+26 -2x=85/(-2) x=-42,5
f) 45x-19=19x-45 45x-19x=-45+19 26x=-26/26 x=-1
g) 82x-9=-18x+1 82x+18x=1+9 100x=10/100 x=0,1